Эффективность использования различных видов ферромагнетиков в линейных импульсных электромеханических преобразователях индукционного и электромагнитного типов - Болюх, Владимир Федорович; Кочерга, Александр Иванович (НТУ "ХПИ", 2017)
Установлен характер распределения индукции магнитного поля в линейных импульсных электромеханических преобразователях (ЛИЭП) индукционного и электромагнитного типов при использовании для ферромагнитного якоря и экрана реальной стали, магнитодиэлектрика и идеальной стали, которые имеют нулевую электропроводность. Установлено влияние видов ферромагнитных материалов на их электромеханические характеристики. Предложены интегральный показатель эффективности, учитывающий КПД, скоростные, силовые и электрические показатели ЛИЭП, и варианты стратегии оценки эффективности. Показано, что по всем вариантам стратегии наименее эффективным является ЛИЭП электромагнитного типа, якорь и ферромагнитный экран (ФЭ) которого выполнены из магнитодиэлектрика. Установлено, что ФЭ ЛИЭП индукционного типа целесообразно изготавливать из реальной стали, а ФЭ и якорь ЛИЭП электромагнитного типа целесообразно изготавливать из идеальной стали, которая имеет минимальную электропроводимость.

The aim of the article is to estimate the influence of the type of ferromagnet - magnetodielectric, ideal and real steel, on the power, speed and electrical parameters of the linear pulsed electromechanical converter (LPEC) of induction and electromagnetic types. Methodology. The mathematical model of LSET using the finite element method, which takes into account spatio-temporal electromagnetic and electromechanical parameters and indices, is developed and implemented in the Comsol Multiphysics software package. The integral efficiency index has been introduced, taking into account the power, speed, energy, and environmental (induction of the magnetic scattering field) indicators. Results. A mathematical model of the LPEC has been developed, which describes fast and interconnected electromagnetic and electromechanical processes, manifested when the armature moves relative to the inductor. The character of the magnetic field induction distribution in LPEC of induction and electromagnetic types is established when using for a ferromagnetic anchor and a screen of real steel, a magnetodielectric and an ideal steel that have zero electrical conductivity. For these LPEC versions, the influence of the types of ferromagnetic materials on their electromechanical characteristics has been established. An integral efficiency index is proposed that takes into account the efficiency, speed, power and electrical parameters of the LPEC, and variants of the efficiency evaluation strategy. It is shown that for all strategy options the least effective is the LPEC of electromagnetic type, the armature and screen of which are made of a magnetodielectric. It is established that the induction-type LPEC screen should be made of real steel, and the screen and the electromagnetic-type LPEC anchor should be made of an ideal steel that has a minimum electrical conductivity. Originality. It was established for the first time that the least effective is a LPEC of electromagnetic type, the armature and screen of which are made of a magnetodielectric. Ferromagnetic screen LPEC induction type is expedient to make of real steel, and the shield and the anchor of LPEC electromagnetic type is expediently made of an ideal steel that has a minimum electrical conductivity. Practical value. The character of the magnetic field induction distribution in LPEC of induction and electromagnetic types is established when using for a ferromagnetic anchor and a screen of real steel, a magnetodielectric and an ideal steel that have zero electrical conductivity. For these LPEC versions, the influence of the types of ferromagnetic materials on their electromechanical characteristics has been established. An integral efficiency index is proposed that takes into account the efficiency, speed, power and electrical parameters of the LPEC, and variants of the efficiency evaluation strategy.
Efficiency of use of various types of ferromagnets in linear pulse electromechanical converters of induction and electromagnetic types
Keywords: сталь реальная; магнитодиэлектрик; сталь идеальная; real steel; magnetodielectric; ideal steel